Carboxymethylpachymaran entrapped plant-based hollow microcapsules for delivery and stabilization of β-galactosidase. Issue 8 (17th July 2019) - Deng, Ziyu; Pei, Yaqiong; Wang, Shishuai; Zhou, Bin; Li, Jiwei; Hou, Xinyao; Li, Jing; Li, Bin; Liang, Hongshan
Abstract : β-Galactosidase (β-Gal) as a dietary supplement can alleviate symptoms of lactose intolerance. Abstract : β-Galactosidase (β-Gal) as a dietary supplement can alleviate symptoms of lactose intolerance. However, β-Gal is deactivated due to the highly acidic conditions and proteases in the digestive tract. In this work, β-Gal was encapsulated into L. clavatum sporopollenin exine capsules (SECs) to fabricate an oral-controlled release system and increase the stability of β-Gal in the digestive tract. The SEC extraction process was optimized. A 3-hour vacuum loading was determined as the optimal loading time. Five different initial ratios of SECs : β-Gal were optimized with the maximum enzyme retention rate reaching 79.40 ± 1.96%. Furthermore, β-Gal-loaded SECs entrapped in carboxymethylpachymaran (CMP) could control the release of β-Gal under simulated gastrointestinal conditions (SGC). The optimal enzyme retention rate reached 65.33 ± 1.46% within 24 h under SGC. Collectively, these results indicated that the entrapped SECs could be used as an effective oral delivery vehicle of β-Gal to improve its performance as a dietary supplement in the digestion of lactose.